The brains project reflection and intervention alignment workshop: Gender and social inclusion report - Nchanji, Eileen; Ketema, Dessalegn (2025)
The BRAINS Project Reflection and Intervention Alignment Workshop, held from August 10–14, 2025, in Kampala, brought together representatives from 14 participating countries, including teams from the Alliance of Bioversity International and CIAT/PABRA, ICIPE, and Gender and National Agricultural Research Systems (NARS) legume coordinators. The workshop’s central theme - Strengthening Collaboration and Gender-Responsive Innovation for Impact - provided a platform to review gender integration progress across value chains and to realign country level interventions toward more inclusive, and gender transformative outcomes. A session with country teams led to the development of socio-technical innovation bundles where social innovations where prioritized and also gender alignment across the country discussed. Intervention Alignment Discussion Questions.docx The gender sessions, led by Dr. Eileen Nchanji, assisted by Dr Dessalegn Ketema. It focused on deepening participants’ understanding of gender concepts beyond equality and equity to transformation and intersectionality (including disability and social inclusion). The session emphasized that while technology and technical innovations remain essential, embedding social innovations within Socio-Technical Innovation Bundles (STIBs) is crucial to achieving equitable and sustainable impact. Country reflections - OneDrive. There were also reflections on how good we are fairing in collecting sex and gender disaggregated data. The second gender session focused on strategic gender research where partners had to carry out advocacy, leadership and couple training in the field. A presentation on what this entails to be used and targets to achieve where discussed. The gender team has developed three gender tools - Advocacy Training Tool, Couple Training Tool, and the Leadership Development Training Manual and shared for review by gender focal teams for ownership and sustainability. These will serve as practical instruments to guide capacity building and gender transformative research across BRAINS country programs.